2019
DOI: 10.1016/j.jep.2019.03.047
|View full text |Cite
|
Sign up to set email alerts
|

The up-regulation of two identified wound healing specific proteins-HSP70 and lysozyme in regenerated Eisenia fetida through transcriptome analysis

Abstract: A B S T R A C TEthnopharmacological relevance: Disposed earthworm has been used to treat various common ailments including burns, arthritis, itching, and inflammation for thousands of years in China. As their remarkable ability to fully regenerate in a scar-free manner, regenerated tissue homogenate of amputated Eisenia fetida (E. fetida) have been considered as an excellent wound repair therapy in our previous study. We have demonstrated that regenerated earthworm (G-90') can perform higher wound repair abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The findings of KEGG pathway analysis of annotated differential gene expression (DGE) in the present study were similarl to that observed in earthworm, Eisenia fetida during regeneration experiment conducted by Yang and coworkers (2019) [ 33 ], indicating that these pathways were essential to begin cellular and metabolic processes, signal transduction for regeneration. The peculiar observation on down regulation instead of upregulation of expression of spliceosomes, ubiquitin mediated proteolysis, cytoskeleton proteins, exosome pathways in regenerated LM samples, could be due to lack of inclusion of at least triplicate samples for analysis of DGE in LM sample.…”
Section: Discussionsupporting
confidence: 90%
“…The findings of KEGG pathway analysis of annotated differential gene expression (DGE) in the present study were similarl to that observed in earthworm, Eisenia fetida during regeneration experiment conducted by Yang and coworkers (2019) [ 33 ], indicating that these pathways were essential to begin cellular and metabolic processes, signal transduction for regeneration. The peculiar observation on down regulation instead of upregulation of expression of spliceosomes, ubiquitin mediated proteolysis, cytoskeleton proteins, exosome pathways in regenerated LM samples, could be due to lack of inclusion of at least triplicate samples for analysis of DGE in LM sample.…”
Section: Discussionsupporting
confidence: 90%
“…Earthworm fibrinolytic proteins were mainly extracted from Lumbricus rubellus , Eisenia fetida , and Pheretima sp. in the former research ( Trisina et al, 2011 ; Yang et al, 2019 ). Pheretima vulgaris Chen ( P. vulgaris ), widely used in China, is a species of earthworm in the Chinese pharmacopoeia and has been rarely studied.…”
Section: Introductionmentioning
confidence: 85%
“…As early as 2010, the National Health Commission of P. R. China issued a document allowing lysozyme to be used as a food additive. In addition, lysozyme is clinically available to promote the repair of injured tissues, to correct the degree of immune activation, and to reduce the acute inflammatory reaction, especially in burn wound infection and herpes treatment [4]. Lysozyme has a globular fold divided into two domains, whose native conformation displays four α-helix structures and a three-strand antiparallel β-sheet [5] which consist of 129 amino acid residues, including six Trp residues, three of which (Trp 62, Trp 63, and Trp 108) locate in the active pocket of the helices domain of lysozyme [6].…”
Section: Introductionmentioning
confidence: 99%